Rapid and effective removal of copper, nitrate and trichloromethane from aqueous media by aluminium alloys - Zhang, Jingqi; Song, Ying; Chao, Jingbo; Huang, Hai; Liu, Dazhi; Coulon, Frederic; Yang, Xiao Jin (Elsevier, 2024)
Zero-valent iron (ZVI) has been extensively studied for its efficacy in removing heavy metals, nitrate, and chlorinated organic compounds from contaminated water. However, its limited effectiveness due to rapid passivation and poor selectivity is prompting for alternative solutions, such as the use of aluminium alloys. In this study, the efficacy of five distinct aluminium alloys, namely Al–Mg, Al–Fe, Al–Cu, and Al–Ni, each comprising 50 % Al by mass at a concentration of 10 g/L, was assessed using copper, nitrate and trichloromethane (TCM) as model contaminants. Results show that chemical pollutants reacted immediately with Al–Mg. On the contrary, the remaining three alloys exhibited a delay of 24 h before demonstrating significant reactivity. Remarkably, Al–Mg alloy reduced nitrate exclusively to ammonium, indicating minimal preference for nitrate reduction to N2. In contrast, the Al–Cu, Al–Ni, and Al–Fe alloys exhibited N2 selectivity of 3 %, 5 %, and 19 %, respectively. The removal efficiency of copper, nitrate and TCM reached 99 % within 24 h, 95 % within 48h and 48 % within 48h, respectively. Noteworthy findings included the correlation between Fe concentration within the Al–Fe alloy and an increased N2 selectivity from 9.3 % to 24.1 %. This resulted in an increase of Fe concentration from 10 % to 58 % albeit with a concurrent reduction in reactivity. Cu2+ removal by Al–Fe alloy occurred via direct electron transfer, while the removal of nitrate and TCM was facilitated by atomic hydrogen generated by the alloy's hydrolysis. Intriguingly, nitrate and TCM suppressed Cu2+ reduction, whereas Cu2+ improved nitrate reduction and TCM degradation. These findings demonstrate the great potential of Al–Mg and Al–Fe alloys as highly efficient agents for water remediation.
Keywords: Aluminum alloys; Nitrate; Copper; Trichloromethane; Pretreatment